EXPRESSION OF SURVIVIN AND E-CADHERIN IN BREAST CANCER - 田晓峰 刘继红 王丽芬 冯晓梅 姚继红 (Chinese journal of cancer research, 2005)
Objective: Survivin is a member of the inhibitor of apoptosis (lAP) family, and is involved in the regulation of cell division. E-cadherin functionally belongs to transmembrane glycoproteins family, it is responsible for intercellular junction mechanism that is crucial for the mutual association of vertebrate cells. These genes are thought to be associated with cancer aggression. This study was to investigate the relationship between surviving gene, E-cadherin expression and invasion clinicopathological features of breast cancer. Methods: The expression of surviving gene and E-cadherin were detected by SP immunohistochemical technique in tissues of 66 breast cancer, 20 breast fibroadenoma and 20 adjacent breast tissue. Results: The positive rate of surviving gene expression in breast cancer was 42.2%, significantly higher (P=0.025) than those in breast fibroadenoma (35.0%), and adjacent breast tissue (10.0%). The positive rate of E-cadherin in the groups of adjacent breast tissue, breast fibroadenoma and breast cancer were 100%, 100% and 42.4%, there was significant difference between the group of benign and malignant tumor (P=0.005). The positive rate of surviving in breast cancer with local lymph node metastasis was significant higher than that in breast cancer without lymph node metastasis (P=0.01), and E-cadherin in breast cancer with local lymph node metastasis was significant lower than that without lymph node metastasis (P=o.ol). There was no significant difference among the groups of pathological types and TNM stages in the expression of surviving (P=0.966 & P=0.856), but there was significant difference in the expression of E-cadherin among these groups (P=0.01 & P=0.023). Conclusion: The loss or decrease of E-cadherin expression may promote the exfoliation of cancerous cells from original tissues, and surviving gene may promote the viability of the exfoliated cancer cells and the formation of new metastasis focus. These 2 factors cooperate with each other in the process of metastasis and invasion. They have a close relation with the breast cancer clinicopathological features.